Centrifugo-pneumatic multi-liquid aliquoting – parallel aliquoting and combination of multiple liquids in centrifugal microfluidics1. Issue 15 (7th August 2015) - Schwemmer, F.; Hutzenlaub, T.; Buselmeier, D.; Paust, N.; von Stetten, F.; Mark, D.; Zengerle, R.; Kosse, D.
<x xml:space="preserve">Abstract</x> The centrifugo-pneumatic multi-liquid aliquoting allows for parallel aliquoting of two liquids and pairwise combination of generated aliquots.